2021
DOI: 10.21203/rs.3.rs-97809/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation on the characteristics of gut microbiome in polycystic ovary syndrome rats induced by dihydrotestosterone or letrozole

Abstract: Background: Etiology of polycystic ovary syndrome (PCOS) is unclear. Recent reports indicated that gut microbiota regulates metabolism and plays a major role in the development of PCOS. The present study aimed to investigate and compare the effects of dihydrotestosterone or letrozole on the gut microbiome in rats.Methods: We used dihydrotestosterone (DHT) or letrozole (LET) to induce PCOS model rats. At the end of the experiment, ovarian morphology, hormonal and metabolic status were investigated in all rats. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
(35 reference statements)
2
0
0
Order By: Relevance
“…19 These changes in the levels of sex- Further studies on rat model have reported increased weight gain on induction of DHT/letrozole in rats after few weeks. 22,23 This was in accordance with a human study on normal weight women where HA caused increased abdominal fat storage and subsequently IR. 24,25 In fact, a recent study found that dysbiosis of the gut microbiota caused by androgens may exacerbate metabolic as well as endocrine function in PCOS 19 and exposure to a healthy gut flora protected a PCOS mouse model from developing metabolic abnormalities.…”
Section: Hyperandrogenism and Microbiomesupporting
confidence: 89%
See 1 more Smart Citation
“…19 These changes in the levels of sex- Further studies on rat model have reported increased weight gain on induction of DHT/letrozole in rats after few weeks. 22,23 This was in accordance with a human study on normal weight women where HA caused increased abdominal fat storage and subsequently IR. 24,25 In fact, a recent study found that dysbiosis of the gut microbiota caused by androgens may exacerbate metabolic as well as endocrine function in PCOS 19 and exposure to a healthy gut flora protected a PCOS mouse model from developing metabolic abnormalities.…”
Section: Hyperandrogenism and Microbiomesupporting
confidence: 89%
“…Infusion of microbes from healthy individual into the PCOS rats showed improved estrous cycle, decreased androgen production, and normalized ovarian morphology implying a link between HA and microbiota composition in PCOS 20,21 . Further studies on rat model have reported increased weight gain on induction of DHT/letrozole in rats after few weeks 22,23 . This was in accordance with a human study on normal weight women where HA caused increased abdominal fat storage and subsequently IR 24,25 .…”
Section: Hyperandrogenism and Microbiomesupporting
confidence: 85%